Dysfunctional parenting styles and maladaptive emotional behaviors in adolescents of a school in South Lima - Canessa Cárdenas, Andrea Marina (2020)
The aim of this research is to determine the relationship existing between the dysfunctional parenting styles perceived and maladaptive emotional behaviors in 2nd, 3rd, and 4th year students of a secondary school in South Lima. The sample consisted of 284 students of both sexes, between 13 and 15 years old. It was a non-experimental type research with a correlational design. To measure the variables, two scales were used: the first one was the Measure of parental styles (MOPS), and the second was the Rating scale for maladaptive emotional behavior of children and adolescents (API-N). The result obtained confirmed the general hypothesis, showing the existence of a highly significant correlation between the dysfunctional parenting style of the father and the maladaptive emotional behavior of the adolescents (.344**), as well as between the dysfunctional parenting style of the mother and  the maladaptive emotional behaviors (.385**). Moreover, a significant correlation was found among the various dimensions of the variables, except for the indifference style of both the father and the mother with the autonomic scale, and of the mother’s indifference style with the emotional scale.